Automated Humidity Control System with Arduino for Indoor Environments - Viana, Filipe Ferreira; Caldeira, Jéssica Nayara Fernandes (Anais do Workshop de Sistemas de Informação (WSIS); 2024: Anais do XV Workshop de Sistemas de InformaçãoDO - 10.5753/wsis.2024.33678, 2024)
This study proposes the development of an automated humidity control system using Arduino, aimed at maintaining healthy humidity levels in indoor environments, especially during the winter. The circuit was designed and simulated using Fritzing software, integrating a humidity sensor, LCD display, and relay module. After the simulation, the system was assembled with low-cost components and tested to ensure the accuracy of the readings and the efficiency in controlling the humidifier. The results showed that the system is capable of monitoring and adjusting humidity in real-time, promoting energy savings and sustainable operation. The system was integrated into a custom case, ensuring protection of the components and ease of use.